Factors influencing surgical outcome of intradural spinal tumors: a prospective study (Nepal Journal of Neuroscience, 2026)
Introduction: Intradural tumors are a diverse group of neoplasms that occur within the dural sac, which can be either intramedullary or extramedullary, representing 40% of all spinal tumors.Methods: This was a prospective study conducted at Bir Hospital. 45 patients with intradural spinal tumors who underwent surgical intervention were included. Preoperative neurological status and postoperative neurological outcome were assessed using the Modified McCormick Scale (MMS). Spearman’s correlation test was done for continuous variables and Fisher’s exact/ Kruskal-Wallis test for categorical variables. The change in MMS from pre-operative assessment to the end of follow-up was assessed using Wilcoxon’s signed rank test. P-value